Bacterial and Antibiotic Susceptibility Patterns in Patient with Pediatric Urinary Tract Infection at Dr. Hasan Sadikin General Hospital - Muhammad Ilham Muttaqin; Dany Hilmanto; Neneng Syarifah Syafei (Althea Medical Journal, 2017)
Background: Pediatric urinary tract infection (UTI) should become attention due to high prevalence, severe complication, and high cost treatment. Bacterial pattern and its susceptibility are different in every region.The objective of this study was to discover pattern of bacteria causing UTI and their susceptibility to antibiotics. Methods: This study was an observational descriptive study. The data was obtained from medical records and susceptibility testing results of pediatric UTI in Department of Child Health at Dr. Hasan Sadikin General Hospital in period of 2014. Data taken was presented in table.Results: There were 26 cultures which had microbiological findings among 79 cultures taken from 106 patients with UTI. The majority of findings were Escherichia coli (10 cases), Pseudomonas aeruginosa (4 cases), and Klebsiella pneumoniae (4 cases). Antibiotic classes with high susceptibility level were aminoglycoside, sulfonamide, and fluoroquinolone. Resistance level were higher in cephalosporin class than others.Conclusions: Most common bacterial found are Escherichia coli, Pseudomonas aeruginosa, and Klebsiellapneumoniae. The result of susceptibility testing for cultures shows variance of susceptibility pattern to antibiotics in pediatric patients with UTI at Department of Child Health Dr. HasanSadikin General Hospital. [AMJ.2017;4(1):52–7] DOI: 10.15850/amj.v4n1.1021